Jokowi’s Loyal Opposition: Analysis of the Model of the Possibility of the Prosper Justice Party to the GovernMent (2014- 2021) - IN’AMUL MUSTOFA; TITIN PURWANINGSIH; RIDHO AL HAMDI (Jurnal Studi Pemerintahan, 2023)
After the 2014 general election and through 2021, the Prosperous Justice Party (PKS) decided to become the executive power’s loyal opposition under President Joko Widodo. PKS’s decision to join an opposition party resulted in a substantial increase in its vote total, from 6.79% in the 2014 election to 8.21% in the 2019 election. There are hints that PKS intends to replicate the strategy employed by the Indonesian Democratic Party of Struggle (PDIP), which be- came President Susilo Bambang Yudhoyono’s opposition during his two terms in office and won the 2014 election. Using secondary data and qualitative descriptive analysis, this study examines the model and pattern of PKS opposition to the Jokowi administration between 2014 and 2021. This study’s findings indicate that the relationship model between PKS and the government is cooperative rather than antagonistic. As an opposition party under a presidential system, PKS works as a balancer and controller of power through selective rather than universal criticism of government policies and performance.